UPSKILL MATH PLUS
Learn Mathematics through our AI based learning portal with the support of our Academic Experts!
Learn moreBased on the three basic trigonometric ratios \(\sin\), \(\cos\) and \(\tan\) we will define its reciprocals.
Reciprocal Ratios:
Consider a right-angled triangle with a corresponding angle \(\theta\).
The three basic trigonometric ratios are:
- Sine
- Cosine
- Tangent
The table below depicts the relation of reciprocal ratios with the right-angled triangle.
Name of the angle | Sine | Cosine | Tangent |
Short form of the angle | \(\sin\) | \(\cos\) | \(\tan\) |
Relationship | \(\sin \theta\) \(=\) \(\frac{\text{Opposite side}}{\text{Hypotenuse}}\) | \(\cos \theta\) \(=\) \(\frac{\text{Adjacent side}}{\text{Hypotenuse}}\) | \(\tan \theta\) \(=\) \(\frac{\text{Opposite side}}{\text{Adjacent side}}\) |
Name of the reciprocal angle | Cosecant | Secant | Cotangent |
Short form of the angle | \(\text{cosec}\) | \(\sec\) | \(\cot\) |
Measurements related to the right-angled triangle | |||
Relationship | \(\text{cosec}\,\theta\) \(=\) \(\frac{\text{Hypotenuse}}{\text{Opposite side}}\) | \(\sec \theta\) \(=\) \(\frac{\text{Hypotenuse}}{\text{Adjacent side}}\) | \(\cot \theta\) \(=\) \(\frac{\text{Adjacent side}}{\text{Opposite side}}\) |
Relation with the basic ratio | \(\text{cosec}\,\theta\) \(=\) \(\frac{1}{\sin \theta}\) or \(\sin \theta\) \(=\) \(\frac{1}{\text{cosec}\,\theta}\) | \(\sec \theta\) \(=\) \(\frac{1}{\cos \theta}\) or \(\cos \theta\) \(=\) \(\frac{1}{\sec \theta}\) | \(\cot \theta\) \(=\) \(\frac{1}{\tan \theta}\) or \(\tan \theta\) \(=\) \(\frac{1}{\cot \theta}\) |
We can write certain identities based on these relationships.
- Identity \(1\):
\(\text{cosec}\,\theta \times \sin \theta\) \(=\) \(\text{cosec}\,\theta \times \frac{1}{\text{cosec}\,\theta}\)
\(=\) \(1\)
Therefore, \(\text{cosec}\,\theta \cdot \sin \theta= 1\).
- Identity \(2\):
\(\sec \theta \times \cos \theta\) \(=\) \(\sec \theta \times \frac{1}{\sec \theta}\)
\(=\) \(1\)
Therefore, \(\sec \theta \cdot \cos \theta = 1\).
- Identity \(3\):
\(\cot \theta \times \tan \theta\) \(=\) \(\cot \theta \times \frac{1}{\cot \theta}\)
\(=\) \(1\)
Therefore, \(\cot \theta \cdot \tan \theta = 1\).